(untitled) (Quest Journal of Management and Social Sciences, 2025)
Background: Information and Communication Technology (ICT) has become essential for improving efficiency, communication, and competitiveness in modern businesses. However, many SMEs in Nepal still face challenges in adopting digital tools due to limited infrastructure, skills, and resources. Purpose: The purpose of the study is to identify the overall situation of ICT adoption in Small and Medium Enterprises in Nepal. Design/methodology/approach: This study is based on the Technological Acceptance Model. This model posits that perceived usefulness and perceived ease of use are two key factors that influence people’s acceptance and use of technology. Using a structured questionnaire, data were collected from a primary source. In this study, convenience sampling techniques were employed, with 408 respondents included in the study. Data collection is conducted using the KOBO Toolbox. Structural Equation Modeling is used to examine the overall situation of ICT adoption through descriptive and inferential analysis. The research is based on an explanatory research design. Findings: The study tested twelve hypotheses related to firm size, resources, perceived usefulness, ease of use, attitude towards using, and actual use behavior. In my research, H1, H4, H11, and H12 do not support the test, and the remaining hypotheses have a significant relationship. The majority of the respondents face the challenge of a lack of knowledge about information communication. Conclusion: The findings of the study indicate that employees of the SEMs have a positive behavioral intention, influenced by firm size and available resources. The organization should prioritize enhancing technological literacy and ensuring that its human resources are adequately skilled. There should be proper data security and government support. For the better adoption of ICT by SMEs Keywords: Information communication technology, small and medium enterprise, behavior intention, actual use behavior, attitude and ease of use.